Applications and implications of whole-slide imaging in breast pathology. Issue 3 (March 2022) - Millican-Slater, Rebecca A.; Rakha, Emad A.
Abstract: Technological advances in whole slide imaging (WSI) technology and artificial intelligence (AI) applications in recent years have resulted in increasing adoption of this paradigm shift technology. This brings with it many advantages, new challenges, and potential adaptations to the microscopic assessment of specimens that pathologists need to be aware of. This article describes the applications and implications of WSI within the context of the reporting of breast pathology specimens. Challenging diagnostic entities in digital breast pathology are presented and the key areas in which AI could be useful in breast pathology are highlighted.